Evaluation of Antimicrobial Usage in Dogs and Cats at a Veterinary Teaching Hospital in Germany in 2017 and 2018 - Schnepf, Anne; Kramer, Sabine; Wagels, Rolf; Volk, Holger A.; Kreienbrock, Lothar (Frontiers in Veterinary Science, 2021)
In contrast to food-producing animals, where the documentation of the usage of antimicrobials is regulated by law, antimicrobial usage (AMU) in dogs and cats is only sparsely monitored. We collected data generated by an electronic practice management software (EPMS) between January 1, 2017, and December 31, 2018, to investigate AMU. All information was obtained from clinical routine data from the Department of Small Animal Medicine and Surgery (DSAM), University of Veterinary Medicine Hannover (TiHo). In 2017, 78,076 drug administrations were documented for 5,471 dogs and cats, of which 14,020 (17.96%) were antimicrobial drugs (AMs) specifically documented in 2,910 (51.31%) dogs and cats. In 2018, 104,481 drug administrations were documented for 5,939 dogs and cats. Of these drug administrations, 18,170 (17.39 %) AM administrations were documented for 3,176 (53.48 %) dogs and cats. Despite the increasing documentation of AM administrations, differences between 2017 and 2018 were not significant (Odds Ratio (OR) 1.01; 95 % Confidence Interval (CI) 0.98 – 1.03). As well as the documented number of AM administrations, the documented amount of active ingredients administered in 2018 (total: 17.06 kg; dogs: 16.11 kg, cats: 0.96 kg) increased compared to 2017 (total: 15.60 kg; dogs: 14.80 kg, cats: 0.80 kg). In 2017 and 2018, the most commonly administered antimicrobial groups were penicillins, nitroimidazoles and quinolones for dogs and cats, respectively. While the in-house point of care administration accounts for the largest share of the documented amount of AMs administered, the highest number of documented AM administrations was assigned to inpatient care in 2017 and 2018, respectively. However, AM administration in outpatient care remained the lowest in both years. Since no significant difference in AM administrations was observed between 2017 and 2018 and the most commonly used AMs at the DSAM were ranked, data can be used as a baseline to evaluate how changes in in-house guidelines and future legal requirements affect the prescribing culture. Data generated within the DSAM should be evaluated annually.